Vulnerability in the context of HIV and syphilis infection in a population of men who have sex with men (MSM) in Salvador, Bahia State, Brazil - Sandra Brignol; Inês Dourado; Leila D. Amorim; Lígia Regina Franco Sansigolo Kerr (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Social, individual, and programmatic vulnerability of men who have sex with men (MSM) in the context of the HIV epidemic and other sexually transmitted infections (STI) is a reality in many countries. The survey Behavior, Attitudes, Practices, and Prevalence of HIV and Syphilis in Men Who Have Sex with Men in 10 Brazilian Cities selected 383 MSM in the city of Salvador, Bahia State, Brazil, using the respondent driven sampling (RDS) technique. Individual vulnerability: early sexual initiation (51%), average of eight sex partners, and unprotected receptive anal sex with casual (32%) and steady partners (45%) and positive rapid tests HIV (6.5%) and syphilis (9%). Social vulnerability: young adults (80%), black race/skin color (91%), mean monthly family income of BRL 1,000.00, and personal history of discrimination (57%). Programmatic factors: no previous HIV test (63%) and no access to lubricant gel (88%). The study showed a profile of vulnerability and the urgent need for interventions and STI prevention in the MSM population in Salvador, in addition to high prevalence rates for HIV and syphilis.